Meningkatan Literasi Teknologi Drone Melalui Pelatihan Dasar Bagi Siswa DKV SMK Negeri 5 Palangka Raya - Zoevans Mart Lumban Tobing; Reihan Zulni; Dera Presta Utama Putra; Said Rizky Bahasyim; Altman Royden; Pernando Sanjaya Doloksaribu; Sherly Katrina; Neny Sukmawati (-, 2026)
Basic drone technology training was conducted to improve Visual Communication Design (DKV) students' understanding and skills in recognizing and operating drones safely and effectively. Pre-test results showed that most students still had limited initial knowledge regarding drone components, flight principles, and safety procedures, and minimal practical experience. The training included an introduction to components, safety rules, flight features, and basic maneuvering practices. Post-test results showed significant improvements in conceptual understanding, mastery of technical terms, safety awareness, and student confidence. These findings confirm that practice-based learning is effective in improving drone technology literacy among DKV vocational high school students.